The impact of piracy on prominent and non-prominent software developers - Alexander Rasch; Tobias Wenzel (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
This paper studies the impact of software piracy on prominent and non-prominent software developers in markets based on a two-sided platform business. Consumer behavior is imperfect and, when adopting a platform, consumers only take prominent software into account. We show that prominent software exhibits higher piracy rates than non-prominent software. However, contrary to intuition, this does not necessarily mean that prominent software developers benefit more from increased software protection. Indeed, we show that prominent developers may lose out whereas non-prominent developers may gain from better software protection.
Keywords: L11; L86; 330; Piracy; Platform; Software; Two-sided market